Blood pressure, pulse rate, and skin temperature during hot-water bathing in real-world settings among community-dwelling older adults: the HEIJO-KYO Study - Yoshiaki Tai; Kenji Obayashi; Kazuki Okumura; Yuki Yamagami; Keigo Saeki (Komiyama Printing Co. Ltd, 2024)
Background: Home hot-tub bathing substantially increases drowning mortality rates among older adults in Japan. Previous laboratory studies on hemodynamic responses during hot-tub bathing have been inconsistent depending on the thermal conditions. Furthermore, real-world hemodynamic changes that occur during bathing remain poorly understood. This study investigated the association between individual thermal states and hemodynamic parameters during hot-tub bathing among community-dwelling older adults. Methods: In this cross-sectional study conducted between January 2016 and April 2019, which involved 1,479 older adults (median [range] age, 68 [40-90] years), skin temperature on the abdominal surface was measured every minute. Ambulatory blood pressure and pulse rate were recorded at 15-min intervals for 24 h. Participants underwent simultaneous living room temperature measurements in their homes, and the time and methods of bathing were recorded. Associations between skin temperature and hemodynamic parameters during bathing and between the pre-bath living room temperature and in-bath maximum proximal skin temperature were evaluated using mixed-effects and linear regression models, respectively. Results: A 1 °C increase in skin temperature was significantly associated with a 2.41 mmHg (95% confidence interval [CI]: 2.03-2.79) increase in systolic blood pressure and a 2.99 bpm (95% CI: 2.66-3.32) increase in pulse rate, after adjusting for potential confounders, including age, sex, body mass index, antihypertensive medication use, dyslipidemia, diabetes, and living room and outdoor temperatures. Significant interactions were not observed between sex and skin temperature in relation to systolic blood pressure and pulse rate (P = 0.088 and 0.490, respectively). One standard deviation lower living room temperature before bathing was significantly associated with a 0.41 °C (95% CI: 0.35-0.47) higher maximum skin temperature during bathing. Conclusions: Our findings suggest that pre-bath cold exposure may increase the skin temperature during hot-tub bathing, possibly resulting in excessive hemodynamic changes. This provides a framework for future interventions that utilize pre-bath thermal conditions and bathing environments to prevent bath-related deaths.